FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR TAHUN 2010-2014 - Sari, Hani Kartika; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Time difference between financial statement date and audit opinion date in the financial statement indicates the length of completion time which is needed by the auditor to finish the audit. The time difference in audit is known as Audit Delay. This research is meant to test the influence of firm size, solvability, profitability, Public Accountant Firm reputation, audit opinion, audit tenure to the audit delay. The population is all manufacturing companies which are listed in the IDX in 2010-2014 periods. The sample collection technique has been carried out by using purposive sampling. Purposive sampling is the sample determination technique with a certain consideration. The amount of samples in one year is 83 companies. The secondary data has been applied in this research in the form of annual financial statement of the company from the IDX. The data analysis technique has been carried out by using multiple linear regressions analysis with significance level 5%. The result of the research shows that variables firm size, profitability, and public accountant firm reputation have negative influence to the audit delay, solvability has positive influence to the audit delay. Audit opinion and audit tenure does not have any influence to the audit delay.Keywords: Audit delay, firm size, solvability, profitability, audit tenure.